Copier des manuscrits : remarques sur le travail du copiste - François Déroche (Revue des Mondes Musulmans et de la Méditerranée)
Professional copyists appeared early on in Muslim societies and they played an important role in the transmission of texts up until the 20th century. Yet, die economic activity around their work is little known. How do these men identify themselves? What were their work conditions? What was their “output”? Information is rare concerning these points but this article tries to bring together data taken from sources and colophons which contain some details about the copyists' work.